Molecular Markers Application for Blast Resistance Selection on the Double Haploid Rice Population (Makara Journal of Science, 2014)
Blast disease, caused by fungal Pyricularia grisea Sacc., is one of the most devastating diseases in rice. The use of blast-resistant rice varieties is one of the most efficient ways to control blast disease in rice. Blast-resistant varieties can be produced through breeding. The use of marker-assisted selection (MAS) available to support selection of resistant lines based on resistance gene. The objective of this research was to compare the resistance response of the double haploid lines with the differential varieties to three selected Indonesian blast races and to identify the resistance genes caused the resistance to blast based on the resistance response and the genotype evaluation using molecular markers. Forty-nine double haploid lines from a double crossing IR54/Parekaligolara//Bio110/Markuti were selected using molecular markers based on the targeted genes Pib, Pi1, Pi2, Pi9, Pi33, Pir4, and Pir7. To compare the phenotype selection, ten LTH monogenic lines of differential varieties were used. All plants tested were inoculated by three selected Indonesian blast races. The results show that the Pib gene caused a resistance to race 123, while the Pi1 and Pir7 genes caused a resistance to race 123 and 133. The Pi2, Pi9, Pi33, and Pir4 genes did not cause a resistance to race 123, 133, or 173.